Analysis of Students' Concept Understanding Ability in View of Mathematical Anxiety in the Implementation of Learning in Class VII of SMP Negeri 1 Mazo - Agnes Rosdiana Telaumbanua; Amin Otoni Harefa; Yulisman Zega (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This research is motivated by the lack of students' ability in understanding concepts so that it has an impact on students in learning mathematics. Because the ability to understand concepts is the basis of understanding principles and theories with the aim of making it easier for students to understand concepts in subsequent material in studying mathematics. One of the factors of the lack of students' ability to understand concepts is math anxiety which has a large influence on student learning processes, both at school and on the student's environment. This study aims to find out how students' conceptual understanding abilities are viewed from mathematics anxiety in the implementation of learning in class VII SMP Negeri 1 Mazo. This type of research is descriptive research with a qualitative approach. This research was conducted at Mazo 1 Public Middle School with a total of 35 research informants. Data collection techniques through written tests, student math anxiety questionnaires, interviews and documentation. Based on the results of the study, it shows that there are students who have the ability to understand mathematical concepts with high anxiety, moderate and low anxiety. Students with high anxiety still cannot solve the test questions in a structured way due to a lack of focus and feeling a little anxious. students who are anxious are students who are good at completing test questions coherently, it's just that there are some that are not done. Students who are low on anxiety, students are able to solve test questions that are given in a structured way because students are calm and don't feel anxious when facing math problems, it's just that they can't finish up to the final result, so that this can have an impact on student learning. So in this case the ability to understand concepts with math anxiety is that the higher the level of students' math anxiety, the lower the students' ability to understand mathematical concepts. Conversely, the lower the students' math anxiety level, the higher the students' understanding of mathematical concepts.